PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PKn MENGGUNAKAN METODE BERMAIN PERAN KELAS V SD - Herlina, Yeni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The purpose of this study was to describe the improvement of student learning outcomes in learning civics Role Playing method in class V SDN 02 West Sikapak Pariaman. The research was conducted at SDN 02 Sikapak West with research subjects were students of class V which amounts to 15 people. RPP cycle assessment results I obtained an average of 73% with both criteria, the second cycle 89% with criteria very well. Aspects of teacher appraisal cycle I gained an average of 73% with both criteria and second cycle 90% obtained with the criteria very well. Student learning outcomes in cycle I gained an average of 66% with sufficient criteria and second cycle 78% with both criteria.   kata kunci: hasil belajar,Pkn,bermain peran.